TRENDS OF CHANGES IN UNEMPLOYEMENT LEVEL IN GEORGIAAND DIRECTIONS OF ITS REGULATION (Globalization and Business, 2018)
Unemployement is the most complex and acute social-economical, demographic, psychological and political problem, which has exclusively negative results. Therefore, unemployement management-regulation is the most significant task of civilized world. Experts’ calculation make it clear, that the problem of unemployement in Georgia is the most acute problem, which has been proved by recent reports of IRI researches performed in Georgia, according to which 40 percent of interviewed population considers, that «The main problem in Georgia is unemployement, and economics is on the second place by 23 percent» . According to the experts“ calculation average rate of unemployement in Georgia is within the limit of 32,0-36,0%. Some experts (I. Archvadze) fix even much higher index (39-40%), to which we agree. As for according to official statistics unemployement rate in 2017 made up in amount of 13,9 percent.In our opinion the significant difference between the rates calculated by official statistics and experts mainly is conditioned by methodological nonsenses ( to consider the owners of land as employed, who work one hour per week, or 4hours per month and 48 hours per year and etc.). It reduces the unemployement rate artificially. For example, in 2017 by official statistics in Guria was fixed the lowest unemployement rate -2,7 percent, which is ridiculous. It is clear and obvious for everyone in Georgia, that by working only one hour per day, a human being cannot earn money even for bread.By the data of International labour organization, in 2017 according to the unemployement rate Georgia had much better (lower) indexes of unemployement rate than Macedony, Greece, Spain, which is rather doubtful.To ensure an effective settlement in Georgia, it is necessary:The first: to unify the efforts of Georgian Parliament, Government, Municipalities, The Ministry of Labour, Healthcare and Social Protection of Geogia and all subordinated services around the basic national strategies which are proved by the Government of Georgia , such as: strategy of Social-economic development of Georgia - «Georgia 2020», strategy of the reform of professional education, complete implementation of «2016-2018 activity plan of the strategy of active policy of Georgian labour market and its implementation». It is rather significant that in the aims of above mentioned strategies the employement and unemployement events are sharply outlined;The second: To develop a new version of a Law project «About employement» and to present it to the Parliament of Georgia to be proved. It is factual, that in Georgia, within the period of acting of the Law «About employement» (in 1991-2006) the government has employed great part of the unemployed people, and protected the definite part of employed people from moving to the unemployed number.The third: according to the regions and considering their specifics processing and implementation of complex programs of employement, in which evaluation cryteria, terms of implementation, financial sources, executors, expected results and etc. would be outlined.The fourth: to create the desirable busness-envi ronment and the legislation base in the country, which will encourage to attract foreign investments, to elaborate and realise effective events for the government to support ( tax benefits, to help in getting cheap credits and etc.) the micro, small and middle business activities.The fifth: To perfect the process of unemployed training, qualification raising and retraining and in general, preparing the professional staff to encrease finansing from the state budget for this purpose;Sixth: To specifying the basic tasks and competences of labour and employement policy Department of the Ministry of Labour, Healthcare and Social Protection according to the goals and demands of the new legislation «About employement» (which should be accepted). Together with developing the employement policy the Ministry should undertake the responsibility of the policy realization as well, which means coordination of the implemented activities for the purpose of employemment and unemployement regulation by the government.Hence it follows, It is not excluded that the necessity of changes of organizational structure of the above mentioned Ministry would be put on the agenda.